How Microcredit Programs Improve Business Household Well-being in the Local Economy? An Impact Evaluation - Nopiah, Ririn; Pasaribu, Esti; Febriani, Ratu Eva (Jurnal Ekonomi Pembangunan, 2024)
Household welfare can be improved through microfinancial institutions' support by providing microcredit programs. The shock of the COVID-19 pandemic caused the impact on household welfare to decrease by 2.6% in 2020 in Bengkulu. This study aims to evaluate the impact of the People's Business Credit (KUR) program on the welfare of business households in Bengkulu Province through the National Socio-Economic Survey of the Central Bureau of Statistics (SUSENAS) for the 2022 wave using the propensity score matching (PSM) method. The study results show that microcredit influences household welfare in Bengkulu. Households receiving KUR had higher expenditures of 8.89% than groups not receiving the KUR program. In addition, age, number of households, education, savings account, marital status, and agricultural business influence KUR program recipient participation. The KUR program is expected to improve the quality of MSMEs and provide recommendations for enhancing KUR program services to related financial institutions.